Perancangan Expert System Diagnosa Anak Penderita Autisme dengan Metode Forward Chaining - Pulungan, Akhiruddin; Wahyu, Fungki; Olivia, Ladyka Febby; Indhira, Sonia; Defit, Sarjon (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Autism disorder in a person is generally suffered from birth, lack of parental sensitivity and knowledge about this is the problem so that the disorder is not detected quickly. For some people who are unfamiliar with this, it is very difficult to find information about places that provide this service. Because the process takes too long, or there is insufficient socialization for parents who do not understand this disorder. With the problems that exist at the Sungai Penuh Special School, Disability Services and Inclusive Education, they are still diagnosed by relying on experts. The author created an expert system that can diagnose children with autism using the forward chaining method, namely by answering questions related to the symptoms of autistic disorders according to the symptoms felt. It is hoped that the Sungai Penuh Special School with Disability Services and Inclusive Education can be helped, and with this system the service will be faster and also help the performance of employees at the Sungai Penuh Special School with Disability Services and Inclusive Education